Molecular Characterization of Biliary Tract Cancer Predicts Chemotherapy and Programmed Death 1/Programmed Death‐Ligand 1 Blockade Responses. Issue 4 (29th July 2021) - Yoon, Jihoon G.; Kim, Min Hwan; Jang, Mi; Kim, Hoguen; Hwang, Ho Kyoung; Kang, Chang Moo; Lee, Woo Jung; Kang, Beodeul; Lee, Choong‐kun; Lee, Min Goo; Chung, Hyun Cheol; Choi, Hye Jin; et al.
Abstract : Background and Aims: Biliary tract cancer (BTC) exhibits diverse molecular characteristics. However, reliable biomarkers that predict therapeutic responses are yet to be discovered. We aimed to identify the molecular features of treatment responses to chemotherapy and immunotherapy in BTCs. Approach and Results: We enrolled 121 advanced BTC patients (68 cholangiocarcinomas [33 intrahepatic, 35 extrahepatic], 41 gallbladder cancers, and 12 Ampulla of Vater cancers) whose specimens were analyzed by clinical sequencing platforms. All patients received first‐line palliative chemotherapy; 48 patients underwent programmed death 1 (PD‐1)/programmed death‐ligand 1 (PD‐L1) blockade therapy after failed chemotherapy. Molecular and histopathological characterization was performed using targeted sequencing and immunohistochemical staining to investigate treatment response‐associated biomarkers. Genomic analysis revealed a broad spectrum of mutational profiles according to anatomical location. Favorable responses to chemotherapy were observed in the small‐duct type compared with the large‐duct type intrahepatic cholangiocarcinoma, with frequent mutations in BRCA1‐associated protein‐1/isocitrate dehydrogenase 1/2 and KRAS proto‐oncogene, GTPase/SMAD family member 4 genes, respectively. The molecular features were further analyzed in BTCs, and transforming growth factor beta and DNA damage response pathway‐altered tumors exhibited poor and favorable chemotherapy responses, respectively. In PD‐1/PD‐L1 blockade‐treated patients, KRAS alteration and chromosomal instability tumors were associated with resistance to immunotherapy. The majority of patients (95.0%) with these resistance factors show no clinical benefit to PD‐1/PD‐L1 blockade and low tumor mutational burdens. Low tumor‐infiltrating lymphocyte (TIL) density in tumors with these resistance factors indicated immune‐suppressive tumor microenvironments, whereas high intratumoral TIL density was associated with a favorable immunotherapy response. Conclusions: This study proposes predictive molecular features of chemotherapy and immunotherapy responses in advanced BTCs using clinical sequencing platforms. Our result provides an intuitive framework to guide the treatment of advanced BTCs benefiting from therapeutic agents based on the tumors' molecular features.